Genome-Wide Linkage Analysis Identifies Loci for Physical Appearance Traits in Chickens - Sun, Yanfa (G3 (Bethesda), 2015)
Physical appearance traits, such as feather-crested head, comb size and type, beard, wattles size, and feathered feet, are used to distinguish between breeds of chicken and also may be associated with economic traits. In this study, a genome-wide linkage analysis was used to identify candidate regions and genes for physical appearance traits and to potentially provide further knowledge of the molecular mechanisms that underlie these traits. The linkage analysis was conducted with an F2 population derived from Beijing-You chickens and a commercial broiler line. Single-nucleotide polymorphisms were analyzed using the Illumina 60K Chicken SNP Beadchip. The data were used to map quantitative trait loci and genes for six physical appearance traits. A 10-cM/0.51-Mb region (0.0−10.0 cM/0.00−0.51 Mb) with 1% genome-wide significant level on LGE22C19W28_E50C23 linkage group (LGE22) for crest trait was identified, which is likely very closely linked to the HOXC8. A QTL with 5% chromosome-wide significant level for comb weight, which partly overlaps with a region identified in a previous study, was identified at 74 cM/25.55 Mb on chicken (Gallus gallus; GG) chromosome 3 (i.e., GGA3). For beard and wattles traits, an identical region 11 cM/2.23 Mb (0.0−11.0 cM/0.00−2.23 Mb) including WNT3 and GH genes on GGA27 was identified. Two QTL with 1% genome-wide significant level for feathered feet trait, one 9-cM/2.80-Mb (48.0-57.0/13.40-16.20 Mb) region on GGA13, and another 12-cM/1.45-Mb (41.0−53.0 cM/11.37−12.82 Mb) region on GGA15 were identified. These candidate regions and genes provide important genetic information for the physical appearance traits in chicken.